Air pollution and the willingness to pay of exposed individuals in downtown Medellín, Colombia (2014)
Within Colombia, Medellín holds the title of the city with the second worst air quality, and within the city, Downtown Medellín is one of the areas most affected by mobile gas emissions. Individuals that work downtown were surveyed in order to measure their willingness to pay (WTP) to reduce air pollution. Four groups are characterized according to the respondents' answers: Stated Preference (SP), Averted Costs (AV), both (SP and AV), and No WTP. Results show that age, income level, having a symptom/illness, and exposure to pollution (at different levels) are important for characterizing the respondents into these groups and have a direct effect on the probability of them stating a positive WTP. © Universidad de Antioquia, 2014